Extra-long Gαs Variant XLαs Protein Escapes Activation-induced Subcellular Redistribution and Is Able to Provide Sustained Signaling - Liu, Zun (American Society for Biochemistry and Molecular Biology, 2011)
Murine models indicate that Gαs and its extra-long variant XLαs, both of which are derived from GNAS, markedly differ regarding their cellular actions, but these differences are unknown. Here we investigated activation-induced trafficking of Gαs and XLαs, using immunofluorescence microscopy, cell fractionation, and total internal reflection fluorescence microscopy. In transfected cells, XLαs remained localized to the plasma membrane, whereas Gαs redistributed to the cytosol after activation by GTPase-inhibiting mutations, cholera toxin treatment, or G protein-coupled receptor agonists (isoproterenol or parathyroid hormone (PTH)(1–34)). Cholera toxin treatment or agonist (isoproterenol or pituitary adenylate cyclase activating peptide-27) stimulation of PC12 cells expressing Gαs and XLαs endogenously led to an increased abundance of Gαs, but not XLαs, in the soluble fraction. Mutational analyses revealed two conserved cysteines and the highly charged domain as being critically involved in the plasma membrane anchoring of XLαs. The cAMP response induced by M-PTH(1–14), a parathyroid hormone analog, terminated quickly in HEK293 cells stably expressing the type 1 PTH/PTH-related peptide receptor, whereas the response remained maximal for at least 6 min in cells that co-expressed the PTH receptor and XLαs. Although isoproterenol-induced cAMP response was not prolonged by XLαs expression, a GTPase-deficient XLαs mutant found in certain tumors and patients with fibrous dysplasia of bone and McCune-Albright syndrome generated more basal cAMP accumulation in HEK293 cells and caused more severe impairment of osteoblastic differentiation of MC3T3-E1 cells than the cognate Gαs mutant (gsp oncogene). Thus, activated XLαs and Gαs traffic differently, and this may form the basis for the differences in their cellular actions.